Formulasi Nanoemulsi Ekstrak Etanol Buah Okra (Abelmoschus esculentus (L.) Moench.) dan Uji Aktifitas Antikolesterol secara In-vitro - Ratna Djamil; Sarah Zaidan; Vera Butar Butar; Diah Kartika Pratami (Fakultas Farmasi Universitas Pancasila, 2020)
Okra fruit has a flavonoid, phytosterol and pectin content, which is potential as an anticholesterol agent. The pharmacological activity of ethanol extract 70 % of okra fruit (EEOF) can be improved by forming nanoemulsion. This study aimed to prepare an ethanol extract 70 % and nanoemulsion of okra fruit and to prove the cholesterol inhibition in vitro EEOF is smaller than the nanoemulsion of EEOF. The okra fruit was extracted by kinetic maceration, the EEOF was analyzed by a phytochemical screening test and cholesterol inhibition assay in vitro using Liebermann-Burchard reagent. The anticholesterol activity was expressed as IC50 values. Nanoemulsion of EEOF prepared by spontaneous emulsification method using capmul, propylenglycol, glycerin (1 : 2.5 : 2 mL). The result of phytochemical screening of okra fruit simplicia and EEOF were contained flavonoid, steroid, triterpenoid, saponin, and coumarin. The resulting nanoemulsion has a 134.7 nm in diameter with a potential zeta value of -26.72 mV. EEOF has IC50 of 764.11 µg/mL and nanoemulsion of EEOF have IC50 of 712.50 µg/mL. Nanoemulsion can improve anticholesterol IC50 value because it was penetrated the gap between cells so that the delivery and bioavailability were higher.